2013
DOI: 10.4103/2152-7806.112605
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological aspects of cerebellopontine neurinoma presenting with recurrent spontaneous bleedings

Abstract: Background:Neurinomas are benign, usually encapsulated, tumors growing in peripheral nerve sheath with a high incidence in the cerebellopontine angle.Case Description:We report a case of vestibular neurinoma (VN) with a “biphasic” pattern of intratumoral hemorrhage presenting with cephalalgia along with progressive ipsilateral mild impairment of both VII and VIII cranial nerves. A thorough preoperative magnetic resonance imaging study better characterized the patchy pattern of the round shaped lesion, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…To date, fewer than 50 cases of hemorrhagic VS have been reported in the English literature . In 2014, Niknafs et al performed a review of the literature and identified 39 cases from 18 published articles .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, fewer than 50 cases of hemorrhagic VS have been reported in the English literature . In 2014, Niknafs et al performed a review of the literature and identified 39 cases from 18 published articles .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases of hemorrhagic VS require prompt surgical intervention because observation and radiosurgery do not alleviate mass effect and risk repeated hemorrhage . Prior to surgery, a focused history and laboratory testing should be obtained to evaluate for primary or acquired bleeding diathesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations